Valuation of Commodity-Based Swing Options - Jaillet, Patrick; Ronn, Ehud I.; Tompaidis, Stathis (Management Science, 2004)
In the energy markets, in particular the electricity and natural gas markets, many contracts incorporate flexibility-of-delivery options known as “swing” or “take-or-pay” options. Subject to daily as well as periodic constraints, these contracts permit the option holder to repeatedly exercise the right to receive greater or smaller amounts of energy. We extract market information from forward prices and volatilities and build a pricing framework for swing options based on a one-factor mean-reverting stochastic process for energy prices that explicitly incorporates seasonal effects. We present a numerical scheme for the valuation of swing options calibrated for the case of natural gas.